MAHASISWA PERBANKAN SYARIAH DI KOTA SEMARANG: STUDI MINAT BERKARIR DI BANK SYARIAH - Suryani Sri Lestari; Siti Hasanah; Saniman Widodo; Mustika Widowati; Mella Katrina Sar (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2026)
ABSTRAK: The purpose of this study is to obtain empirical evidence regarding Sharia Banking Students in Semarang City: a Study of Student Career Interest in Sharia Banking industry. The dependent variable in this study is Student Career Interest in Sharia Banking with independent variables namely Internship Experience, Sharia Banking Knowledge, Motivation and Financial Rewards. The respondent of this study is 75 Sharia Banking Students in Semarang City. The data collection method in this study uses primary data. Data analysis uses Multiple Linear Regression analysis. The results of the hypothesis indicate that Internship Experience, Islamic Banking Knowledge, Motivation, and Financial Rewards simultaneously have a significant effect on career interest in Islamic banking among Islamic Banking Students in Semarang. Partially, the internship experience and motivation variables have a positive and significant effect on career interest in Islamic banking among Islamic Banking students in Semarang. The Islamic banking knowledge variable partially has a positive but insignificant effect on career interest in Islamic banking. Meanwhile, the financial rewards variable has a negative and insignificant effect on career interest in Islamic Banking students in Semarang City.